The Role of Balancing Nanostructured Silicon Anodes and NMC Cathodes in Lithium-Ion Full-Cells with High Volumetric Energy Density. Issue 2 (21st January 2020) - Baasner, Anne; Reuter, Florian; Seidel, Matthias; Krause, Andreas; Pflug, Erik; Härtel, Paul; Dörfler, Susanne; Abendroth, Thomas; Althues, Holger; Kaskel, Stefan
Abstract : Silicon anodes offer a very promising approach to boost the energy density of lithium-ion batteries. While silicon anodes show a high capacity and, depending on the system, a good cycle stability in half-cells vs lithium, their integration in industrially applicable lithium-ion full-cells is still challenging. Balancing described as the capacity ratio of negative and positive electrode (n/p ratio) is a crucial necessity for the successful design of lithium-ion batteries. In this work, three different silicon based anode systems, namely carbon coated silicon nanowires, columnar silicon thin films and silicon-carbon void structures are compared in LIB full cells containing NMC111 cathodes. By varying the areal capacity of the NMC111 cathode, the influence of the balancing was investigated over a broad n/p range of 0.8−3.2. The aim was to find an ideal compromise between lithium plating suppression, high cycling stability and maximized energy density. To underline the high volumetric energy density, the columnar silicon thin films are additionally analyzed in multilayered pouch cells with NMC622 and NMC811 cathodes resulting in 605 Wh L −1 and 135 Wh kg −1 and even 806 Wh L −1 and 183 Wh kg −1 as demonstrated on stack level.